Physiological function and neuromuscular recruitment in elite South African distance runners - Noakes, T. D.; Harley, J. X. R.; Bosch, A. N.; Marino, F. E.; St. Clair Gibson, A.; Lambert, M. (Equine and Comparative Exercise Physiology, 2004)
Physiological studies of elite and sub-elite black South African runners show that these athletes are typically about 10-12 kg lighter than white athletes and that they are able to sustain higher exercise intensities for longer than white runners. Such superior performance is not a result of higher V·O2max values and hence cannot be due to superior oxygen delivery to the active muscles during maximal exercise, as is predicted by the traditional cardiovascular/anaerobic/catastrophic models of exercise physiology. A marginally superior running economy is also unlikely to be a crucial determinant in explaining this apparent superiority. However, black athletes are able to sustain lower rectal and thigh, but higher mean skin, temperatures during exercise. Furthermore, when exercising in the heat, lighter black athletes are able to maintain higher running speeds than are larger white runners matched for running performance in cool environmental conditions. According to the contrasting theory that the body acts as a complex system during exercise, the superiority of black African athletes should be sought in an enhanced capacity to maintain homeostasis in all their inter-dependent biological systems despite running at higher relative exercise intensities and metabolic rates. In this case, any explanation for the success of East African runners will be found in the way in which their innate physiology, training, environment, expectations and genes influence the function of those parts of their subconscious (and conscious) brains that appear to regulate the protection of homeostasis during exercise as part of an integrative, complex biological system.